Non-invasive assessment of pulmonary vein isolation durability using late gadolinium enhancement magnetic resonance imaging. Issue 2 (20th September 2022) - Padilla-Cueto, David; Ferro, Elisenda; Garre, Paz; Prat, Susanna; Guichard, Jean-Baptiste; Perea, Rosario J; Tolosana, Jose Maria; Guasch, Eduard; Arbelo, Elena; Porta-Sanchéz, Andreu; Roca-Luque, Ivo; Sitges, Marta; et al.
Abstract: Aims: Electrical reconnection of pulmonary veins (PVs) is considered an important determinant of recurrent atrial fibrillation (AF) after pulmonary vein isolation (PVI). To date, AF recurrences almost automatically trigger invasive repeat procedures, required to assess PVI durability. With recent technical advances, it is becoming increasingly common to find all PVs isolated in those repeat procedures. Thus, as ablation of extra-PV targets has failed to show benefit in randomized trials, more and more often these highly invasive procedures are performed only to rule out PV reconnection. Here we aim to define the ability of late gadolinium enhancement (LGE)-magnetic resonance imaging (MRI) to rule out PV reconnection non-invasively. Methods and results: This study is based on a prospective registry in which all patients receive an LGE-MRI after AF ablation. Included were all patients that—after an initial PVI and post-ablation LGE-MRI—underwent an invasive repeat procedure, which served as a reference to determine the predictive value of non-invasive lesion assessment by LGE-MRI.: 152 patients and 304 PV pairs were analysed. LGE-MRI predicted electrical PV reconnection with high sensitivity (98.9%) but rather low specificity (55.6%). Of note, LGE lesions without discontinuation ruled out reconnection of the respective PV pair with a negative predictive value of 96.9%, and patients with complete LGE lesion sets encircling all PVs were highly unlikely to show any PV reconnection (negative predictive value: 94.4%). Conclusion: LGE-MRI has the potential to guide selection of appropriate candidates and planning of the ablation strategy for repeat procedures and may help to identify patients that will not benefit from a redo-procedure if no ablation of extra-PV targets is intended.